Active control of metasurface via integrated spintronic terahertz emitter. (16th February 2023) - Feng, Zheng; Wang, Dacheng; Zhang, Caihong; Sun, Song; Xiang, Xingcheng; Jia, Xiaoqing; Jin, Biaobing; Tan, Wei
Abstract: Active metasurfaces have attracted increased attention due to their capabilities in function switching and wavefront shaping. Here we develop a new paradigm for active control of metasurfaces via integrating a tunable and programmable spintronic terahertz emitter (STE). While compatible with almost all conventional materials for metasurfaces, the STE can empower the passive metasurfaces to be active with increased flexibility. For the sake of illustration, a STE integrated metasurface quarter-wave plate is demonstrated, which enables broadband full polarization control over the entire Poincaré sphere. We also share a future perspective that the STE integrated metasurface can be readily programmed by using a commercial spatial light modulator. This work bridges the studies of metasurfaces and spintronic THz emitters, and may inspire more fruitful active metasurface designs and applications.